Roll-over shape of a prosthetic foot: a finite element evaluation and experimental validation - Balaramakrishnan, Thirunindravur Mannan; Natarajan, Sundararajan; Srinivasan, Sujatha (Medical & biological engineering & computing, 2020)
Prosthetic feet have generally been designed experimentally by adopting a trial-and-error technique. The objective of this research is to introduce a novel numerical approach for the a priori evaluation of the roll-over shape (ROS) of a prosthetic foot for application in its systematic design and development. The ROS was achieved numerically by employing a non-linear finite element model incorporating the augmented Lagrangian and multi-point constraint contact formulations, a hyperelastic material model and a higher-order strain definition. The Ottobock Solid Ankle Cushion Heel (SACH) foot was chosen to experimentally validate the numerical model. The geometry of the foot was evaluated from optical scans, and the material properties were obtained from uniaxial tensile, shear and volumetric compression tests. A new setup was designed for an improved experimental determination of the ROS, with the inclusion of an extended moment arm and variable loading. Error analysis of the radius of curvature of the ROS between the numerical and experimental results showed the percentage error to be 7.52%, thereby establishing the validity of the model. A numerical design model of this kind can be utilised to vary the input design parameters to arrive at a prosthetic foot with specified performance characteristics effectively and economically. Graphical abstract